Keragaan Agronomi Galur-galur Kedelai Potensial pada Dua Agroekologi Lahan Kering Masam - Kuswantoro, Heru; ,, Sutrisno; Supeno, dan Agus (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
Performance of soybean growth and development is influenced by environmental conditions. On similar soil fertility conditions but different environmental conditions such as rainfall will also lead the changes in the performance of the plant. The research aimed to study the agronomic performance of the potential soybean lines in two different drought acid land agroecologies. The experiment was conducted at the South Lampung Tegineneng experimental station and East Lampung Taman Bogo experimental station from February until May 2013. The South Lampung Tegineneng experimental station has a pH of 5.50 and an average rainfall of 89 mm per month, and The East Lampung Taman Bogo experimental station has a pH of 5.12 and an average rainfall of 213 mm per month. The experiment consisted of 10 soybean lines adapted acid land and two check varieties. The experiment was arranged in randomized completely block design with four replications. The least significant different test (LSD) at α = 0.05 was used to calculate significant differences among all treatments. The results showed that rainfall influenced agronomic performance of soybean more than soil acidity. The yield performance in South Lampung was lower than in the East Lampung. Four genotypes produced higher grain yield than the Tanggamus variety in both locations, i.e. Tgm/Anj-862, Tgm/Anj-784, Tgm/Anj-888 Tgm/Anj-857, and Tgm/Anj-858. Tgm/Anj-862 was the most superior genotypes for having the highest number of branches, number of pods, and 100-seeds weight and seed yield and consistent at both locations. The four genotypes, especially Tgm/Anj-862, were potential to be developed in both locations or other locations with similar environmental conditions.Keywords: grain yield, ultisol, yield components